Numerical study on operating characteristics of self-driven total heat recovery system for wet-hot flue gas. (5th June 2020) - Zhang, Chenghu; Yang, Yujie; Fan, Lijia; Huang, Xinpeng
Highlights: No external heat source is required for system operation. The system is designed according to the flue gas heat transfer characteristics. Both the latent heat and sensible heat are recovered. The system owns a good heat recovery rate with a high flue gas temperature. Abstract: This paper proposes a self-driven wet-hot flue gas total heat recovery system according to the characteristics of the heat transfer process of flue gas condensation, which uses the sensible heat in the high-temperature section to drive the system and complete the deep waste heat recovery of flue gas. The effect of flue gas and secondary water flow rate, flue gas and secondary water inlet temperature, and flue gas moisture on system performance were investigated and analyzed. Besides, the applicability analysis of technology and economic analysis are also performed. The results show that under the rated working conditions, the flue gas outlet temperature and relative humidity are 41.39 °C and 61.25%, respectively, and the maximum heat recovery rate of the system can reach 11.6%. When the flue gas inlet temperature is increased from 350 °C to 550 °C, the heat exchange capacity of the system is increased by 46%. Besides, when the flue gas inlet parameter is 550 °C/ and 120 g/kg (a), if the expected heat recovery rate of the known project is 10%, the maximum temperature of the secondary water that can be prepared by the self-driving system is 63 °C and the payback time is 2.53 years. When the flue gas inlet temperature and the moisture content is high, the system can provide hot water with higher temperature and is more energy-efficient than the traditional scheme.